Susceptibility to eating disorders among collegiate female student-athletes - McLester, C. N.; Hardin, R.; Hoppe, S. (Journal of Athletic Training, 2014)
Context: Research has suggested that the prevalence of young women with eating disorders (EDs) is increasing, but determining the exact prevalence of EDs within the female student-athlete (FS-A) population is difficult. Looking at certain traits may help us to identify their level of susceptibility to developing an ED.